The Causes of Lack of Pharmaceutical Logistics Monitoring in Surgery Rooms: A Case Study in a Type C Hospital - Iswari, Luh Putu Ayu Pradnya; Youandi, Abdi Agus; Indriani, Wiwin (Fakultas Kedokteran Universitas Brawijaya, 2020)
The surgery rooms have an important role in the hospital, so it must be managed properly. The surgery rooms consume 9% of the annual hospital budget. High operational costs caused by the large cost of human resources, medical materials, and other supporting facilities. This study was conducted in a private hospital type C with 181 beds and has four surgery rooms. The number of patients which was operated in X Hospital was very high, and the highest number in July 2019 reached 515 patients. There were a large supply of drugs and medical devices in the surgery rooms.Â The number of each drug reached hundreds ampoule, and medical devices reached tens and some in the hundreds. The management of pharmaceutical supplies in the surgery rooms was carried out by senior nurse head of surgery rooms. Monitoring logistic by pharmacy officer only done once a month. This made excessive of stock and become expired. The purpose of this study was to analyze the factors that cause the lack of pharmaceutical logistics monitoring in the surgery rooms. Determination the root of the problem was done by using a fishbone diagram through a Focus Group Discussion with the division heads and subdivision heads of X Hospital. Focus Group Discussion is done by asking the participants one by one to find the root of the problem based on five factors (man, material, method, machine, and environment). Obtained 8 root problems then analyzed with 5 why to get the main root problem. Furthermore, determine the biggest problem using the CARL (capability, accessibility, readiness, and leverage) method, with a weighting score between 1-5. The results found that the absence of pharmaceutical logistics monitoring SOP in the surgery rooms was the most contributing factor to the lack of pharmaceutical logistics monitoring in the surgery rooms.